Radiological features in patients with short stature homeobox-containing (SHOX) gene deficiency and turner syndrome before and after 2 years of GH treatment - Child, Christopher J.; Kalifa, Gabriel; Jones, Christine; Ross, Judith L.; Rappold, Gudrun; Quigley, Charmian A.; Zimmermann, Alan G.; Garding, Gina; Jr, Gordon B. Cutler; Blum, Werner F. (Hormone research in paediatrics, 2015)
Background/Aims: The short stature homeobox-containing (SHOX) gene is one of many genes that regulate longitudinal growth. The SHOX deficiency (SHOX-D) phenotype, caused by intragenic or regulatory region defects, ranges from normal stature to mesomelic skeletal dysplasia. We investigated differences in radiological anomalies between patients with SHOX-D and Turner syndrome (TS) and the effect of 2 years of growth hormone (GH) treatment on these anomalies. Methods: Left hand/wrist, forearm and lower leg radiographs were assessed at baseline and after 2 years in children with genetically confirmed SHOX-D (GH-treated and untreated groups) and TS (GH-treated) in a randomised, controlled, multinational study. Results: Radiological anomalies of hand, wrist and forearm were common in SHOX-D and TS. Radial bowing appeared more prevalent in SHOX-D, while lower leg anomalies were more common in TS. There were no significant differences in radiological findings between GH-treated and untreated patients with SHOX-D after 2 years. Conclusion: GH treatment had no systematic effect on skeletal findings in SHOX-D, based on limited radiological differences between the GH-treated and untreated groups at 2 years. Bone age radiographs allow assessment of radiological signs indicating a potential diagnosis of SHOX-D and may lead to earlier genetic confirmation and initiation of GH therapy.
Gesehen am 16.11.2020